Chloride – The Underrated Ion in Nociceptors - Wilke, Bettina U.; Kummer, Kai K.; Leitner, Michael G.; Kress, Michaela (Frontiers in Neuroscience, 2020)
In contrast to pain processing neurons in the spinal cord where the importance of chloride conductances is already well established, chloride homeostasis in primary afferent neurons has received less attention. Sensory neurons maintain high intracellular chloride concentration through balanced activity of Na+-K+-2Cl- cotransporter 1 (NKCC1) and K+-Cl- cotransporter 2 (KCC2). Whereas in other cell types activation of chloride conductances causes hyperpolarization, activation of the same conductances in primary afferent neurons may lead to inhibitory or excitatory depolarization depending on the actual chloride reversal potential and the total amount of chloride efflux during channel or transporter activation. Dorsal root ganglion (DRG) neurons express a multitude of chloride channel types belonging to different channel families such as ligand-gated, ionotropic γ-aminobutyric acid (GABA) or glycin receptors, Ca2+-activated chloride channels of the anoctamin/TMEM16, bestrophin or tweety-homologue family, CLC chloride channels and transporter, cystic fibrosis transmembrane conductance regulator (CFTR) as well as volume-regulated anion channels (VRACs). Specific chloride conductances are involved in signal transduction and amplification at the peripheral nerve terminal, contribute to excitability and action potential generation of sensory neurons, or crucially shape synaptic transmission in the spinal dorsal horn. In addition, chloride channels can be modified by a plethora of inflammatory mediators affecting them directly, via protein-protein interaction or through signalling cascades. Since chloride channels as well as mediators that modulate chloride fluxes are regulated in pain disorders and contribute to nociceptor excitation and sensitization it is timely and important to emphasize their critical role in nociceptive primary afferents in this review.